Motor Speed Control for River Sediment Volume Measurement Using a Fuzzy Logic Controller - Nur Azizah Maghfiroh; Muhammad Kevin Hardiansyah; Sri Arttini Dwi Prasetyowati; Nugroho, Agus Adhi; Bustanul Arifin (International Forum of Researchers and Lecturers, 2025)
The DC motor serves as the main drive of the vessel and is equipped with a rotary encoder that functions to regulate the movement of the sensor in measuring sediment levels. This rotary encoder is also used to monitor and represent the rotational speed of the DC motor. System testing was carried out by implementing a Fuzzy Logic Controller (FLC) algorithm to control the DC motor speed in moving the vessel, ensuring stable motion. This fuzzy logic–based approach is expected to improve accuracy and efficiency in sediment volume calculations, while also reducing potential errors that commonly occur in manual methods. Simulating motor speed control using the fuzzy logic algorithm in MATLAB, the best test results were achieved over several trials, with a rise time of 376.310 ms and an overshoot of 83.33%. Motor speed measurements using both a tachometer and Arduino produced consistent results, with an average relative error of 0.18%.